Pengaruh Love of Money, Locus of Control, Ecerdasan Emosional terhadap Perilaku Etis Mahasiswa Akuntansi - Soemaryono Soemaryono; Rudi Pratono (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The objectives of this research are: 1) To determine the effect of Love of Money on Ethical Behavior in accounting students 2) To determine the effect of Locus of Control on Ethical Behavior in accounting students 3) To determine the effect of emotional intelligence on Ethical Behavior in accounting students. The independent variables in this study are Love of Money, Locus of Control and Emotional Intelligence. while the dependent variable in this study is Ethical Behavior. Sample determination using quantitative methods with total sample sampling. The population used in this study were accounting students at Wijaya Kusuma University Surabaya, totaling 134 people and a sample size of 124 respondents. The analysis technique for Hypothesis Testing uses Multiple Linear Regression. The results showed that Love of money has a significant effect on Ethical Behavior, Locus of control has a significant effect on Ethical Behavior, and emotional intelligence has no significant effect on Ethical Behavior.